ECOLOGICAL AND AESTHETIC EDUCATION STUDENT YOUTH IN THE UK (Pedagogy of Higher and Secondary Education, 2008)
Basic characteristics, principles of Environmental and Aesthetic education through art in Great Britain are examined.